Thermal Performance Assessment of Windcatchers in Tropical Climate: A Case Study in a Single-story Building - Bernal, Ana Leydis; Montilla, Lenin; Chen Austin, Miguel (LACCEI, 2024)
Windcatchers are structures that have been developed primarily in the Middle East, particularly in the country of Iran, throughout history. In recent decades they have spread to countries in Europe and are effective in tropical climates as well. These structures utilize the aerodynamic principles of natural ventilation which results in a practical method to improve occupants’ health by positively influencing air quality and reducing electrical consumption for air conditioning in buildings. Thus, the objective of this study is to evaluate the thermal performance of wind traps, in terms of air renewal rate, operating temperature, and indoor relative humidity, in a climate like that of Panama City using dynamic energy simulation of seven case studies varying their geometry, for a single-family residential building, during days with more and less wind. For a single-family house, case B1 presents the best performance by handling acceptable air exchange rates with relative humidity within comfort parameters. On the other hand, for larger buildings, case B2 presents the best air exchange rates, but with very high relative humidities outside the comfort limit, so another option would be case A2 or C2 which handle air exchange rates a little lower than B2, but with relative humidities within the comfort range.